The Effect of Exogenous Salicylic Acid Application on Capsicum annuum L. Under Drought Stress During the Vegetative Phase - Budiyanti, Tri (Jurnal Sains Agro, 2025)
Chili is one of the commodities with a relatively high level of price fluctuation. The impact of climate change on the agricultural sector is the uncertainty of the dry season, which causes changes in cropping patterns due to drought. Cultivation technology and superior varieties with drought-tolerant characteristics are among the needs for increasing chili production. This activity aims to increase drought stress tolerance in local chili peppers of West Sumatra. The research was conducted from July to December 2024 in Solok, West Sumatra. This research was conducted with a Randomized Complate Block Design (RCBD) with 6 treatments of giving several doses of salicylic acid and repeated as many as 3 replicates. Salicylic acid was sprayed on chili plants aged 14 days after planting (HST) every two weeks with concentrations of 5, 10, 15 mM, as much as 20 mL per plant. The results showed that drought stress, combined with watering at 35% of field capacity, caused a decrease in vegetative and early generative growth in chili plants. Salicylic acid treatment has not been able to increase early vegetative and generative growth in drought-stressed chili plants 2 months after planting